Changes in dermal matrix in the absence of Rac1 in keratinocytes - Stanley, Alanna (J Anat, 2016)
Keratinocytes, in response to irritants, secrete pro‐inflammatory mediators which recruit and activate immune and mesenchymal cells, including fibroblasts, to repair the skin. Fibroblasts respond by synthesising collagen and promoting the crosslinking extracellular matrix (ECM). We recently showed that the deletion of Rac1 in keratinocytes causes heightened inflammation due to aberrant crosstalk with immune cells. Indeed, the skin of these mice shows a higher inflammatory response to the induction of irritant contact dermatitis (ICD), and also even to treatment with a vehicle alone, compared with controls. As inflammation is intimately linked with fibrotic disease in the skin, this raised the question as to whether this deletion may also affect the deposition and arrangement of the dermal ECM. This study assessed the effects of Rac1 deletion in keratinocytes and of the heightened inflammatory status by induction of ICD on the tissue localisation and arrangements of dermal collagen. Qualitative analysis did not reveal evidence for the formation of pathologies in the dermis. However, quantitative analysis did reveal some perturbations in the dermal matrix, namely that only the combination of the lack of Rac1 and ICD affects the architectural organisation of the dermal collagen, and that a higher inflammatory state in the tissue (i.e. when Rac1 is deleted in the keratinocytes or ICD is induced in the skin, or a combination of both) influences the diameter of the collagen fibrils. It is proposed that this increase in the diameter of collagen fibrils due to inflammation may serve as pre‐fibrotic marker enabling earlier determination of fibrosis and earlier treatment. This study has revealed previously unknown effects on the ECM due to the deletion of Rac1 in keratinocytes.